Dialysis Tubing Experiment Showed That Molybdenum Reduction In S. Marcescens Strain Dry6 Is Mediated By Enzymatic Action - Rahman, M.F.; Ahmad, S.A.; Salvam, S.; Halmi, M.I.E; Yusof, M.T.; Shukor, M.Y.; Shamaan, N.A.; M. A. Syed (Hibiscus Publisher, Malaysia, 2024)
Reduction of metal ions by microbes has long been afflicted by the contribution of abiotic and nonabiotic metal-reducing chemicals. The discrimination between enzymatic and chemical action upon metal must be solved to present a clear reduction mechanism. In this work, a previously developed method using dialysis tubing was employed to study the contribution of these agents upon molybdenum reduction to molybdenum blue in S. marcescens strain Dr.Y6. We discovered that approximately 95 % of molybdenum blue formed was found in the inside of the dialysis tubing. This suggests that the reduction of molybdate by this bacterium requires the presence of cells or mediated enzymatically.